Modelling functional motions of biological systems by customised natural moves - Demharter,, S; Knapp, B; Deane, C; Minary, P (Biophysical Society, 2016)
Simulating the functional motions of biomolecular systems requires large computational resources. We introduce a computationally inexpensive protocol for the systematic testing of hypotheses regarding the dynamic behaviour of proteins and nucleic acids. The protocol is based on Natural Move Monte Carlo, a highly efficient conformational sampling method with in-built customisation capabilities that allows researchers to design and perform a large number of simulations to investigate functionalmotions in biological systems. We demonstrate the use of this protocol on both a protein and a DNA case study. Firstly, we investigate the plasticity of a class II major-histo-compatibility complex in the absence of a bound peptide. Secondly, we study the effects of the epigenetic mark 5-hydroxymethyl on cytosine on the structure of the Dickerson-Drew dodecamer. We show how our customised Natural Moves protocol can be used to investigate causal relationships of functional motions in biological systems.